THE EFFECT OF LANGUAGE LEARNING STRATEGY AND TECHNOLOGY TOWARD STUDENTS’ WRITING SKILLS - Asfar Arif Nurharjanto; Agus Widyantoro (Universitas Negeri Yogyakarta, 2020)
This study aims to find relationship between students’ use of language learning strategies and technology to their writing performance. This study sought to find whether there is influence of students’ language learning strategies to their writing skill, students’ technology use to the writing skills, and combination of both to the writing skills. This study was quantitative research. The respondent were 459 high school students from six High schools. The students were 11 grade students in the first semester. The study employed Strategy Inventory Language Learning questionnaire, students’ technology use questionnaire, and a writing test to collect the quantitative data. The instruments were through experts to ensure the validity and reliability. The quantitative data were analyzed using SPSS to look for the regression value between variables. Findings suggest that both language learning strategies and students’ technology use significantly influence their writing performance. Moreover, language learning strategies as well as technology use, when analyzed separately, positively influence students’ writing performance. The findings confirm that including and promoting both language learning strategies and technology use could help student improve their performance in the classroom.